Osobennosti adrenoreaktivnosti eritrotsitov pri ishemicheskoi bolezni serdtsa - Khazhieva E. A., Shamratova V. G. (Education and science in the modern context, 2017)
The paper is dedicated to comparison of adrenal-dependent erythrocyte sedimentation (AES) among women who suffer from ischemic heart disease (IHD) and healthy young women. In cases of IHD, unlike the situation among the healthy young women, distribution by AES type is characterized by predominance of people of the aggregant type and higher average values of AES.
Keywords: ишемическая болезнь сердца; адренореактивность; Adrenoreactivity; ESR; СОЭ; адренозависимое оседание эритроцитов; гипертоническая болезнь; adrenal-dependent erythrocyte sedimentation; hypertonic disease; ischemic heart disease